Pengembangan Perangkat Pembelajaran Matematika Berbasis Penemuan Terbimbing Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas VI SDN 02 Sitiung - Maizar, Maizar; Junaidi, Junaidi; Fatimah, Fatia (Universitas PGRI Madiun, 2023)
Problem-solving abilities aim to increase students' analytical power in making decisions so as to help shape students' perceptions by seeing mathematics as an integrated part of life, but in reality students' problem-solving abilities are not yet optimal, one of the causes is the unavailability of learning tools that facilitate students students to improve their ability to solve mathematical problems. This study aims to produce learning tools based on the guided discovery model to improve students' problem-solving abilities in grade VI elementary school mathematics LKPD. This development research uses the Plomp model which consists of 3 stages, namely, preliminary, prototyping and assessment. The research subjects were students of class VI at SDN 02 Sitiung. Validation was carried out by experts in mathematics education, educational technology, and Indonesian. Practicality of learning tools seen from the results of practicality questionnaires on the implementation of learning, student and teacher questionnaires. Effectiveness is seen from the learning outcomes of students. The results of the analysis of the validity data indicate that the resulting guided discovery model-based learning tools have met the valid criteria in terms of content and construct. The learning tools are practical in terms of implementation, ease and time required, because the developed learning tools can be applied in mathematics learning activities. Learning tools have also been effective because they can improve learning outcomes. Based on these results, it can be concluded that the mathematics learning tools based on the guided discovery model for class VI Semester I that have been produced can be declared valid, practical and effective.